Post-sports career healthy ageing: The Janus-faced, high-performance sport - Lelbach, A.; Dörnyei, G.; Ihász, F.; Kollerakos, A. (Developments in Health Sciences, 2021)
By now, there is no doubt that regular physical exercise has an overall beneficial effect on each organ of the body. However, the effects of highly competitive sports (HCS) are more complex, as they exert greater demands on the cardiovascular and metabolic systems, among others. Strength, athletic, and aesthetic sport types each has a different exercise intensity and nutritional loading, as well as a different prevalence of cardiometabolic diseases at a later age. HCS athletes experience hypertension and mental stress during competitions and high nutritional loads between them. The post-career effects of this behaviour on the heart, arteries, cellular metabolism, and risk of obesity, are not well known and are not often the focus of research. In this review, we aimed to summarize the post-career effects of HCS. Based on data in the literature, we propose that athletes involved in highly competitive strength sports progressively develop metabolic syndrome and sustained elevated blood pressure.